Android-Based Word Composition Game "Ocid Scramble" To Train Deaf People In Composing A Sentence - Hamdani Arif; Muhammad Nashrullah (JOINCS (Journal of Informatics, Network, and Computer Science), 2020)
Deafness is a term commonly used to refer to those who have hearing loss. Deaf people are those who experience problems with damage to the ear organs in the hearing process which causes the organ to malfunction properly, so along with the rapid technological advancement, now a learning media has been widely developed using smartphones especially with the Android operating system and can provide many benefits for users. Android operating system is a mobile operating system that is open source or open. Android provides an open platform for developers to create their own applications for use by various mobile / mobile devices. Referring to the problem above, the writer makes a learning medium in the form of word stacking games based on the android "Ocid Scramble" aimed at training deaf people in composing a structured sentence. The game also has a more interesting and interactive interface so that people with hearing impairment can improve their ability to compile a sentence properly and correctly.